(untitled) (Perioperaciina Medicina, 2019)
Venous thromboembolic complications are potentially dangerous complications to life in patients undergoing surgical intervention. The aim of the work is to study the safety of enoxaparin thromboprophylaxis by eliciting the effect of sodium enoxaparin (Flenox) on the immune system of patients undergoing laparoscopic cholecystectomy. Materials and methods. Study group: (n = 15)– patients who were treated with enoxaparin sodium (Flenox) for venous thromboembolic complications. Study of immunograms in patients with calculous cholecystitis was performed before surgery and after two days in post-operative period after appointment of enoxaparin. Results and discussion. In the study group (Flenox), the values of the studied rates did not go beyond the norm. Conclusions. It was established that sodium enoxaparin (Flenox) does not affect the immune system’s rates. In connection with the above mentioned, this medicine can be considered safe and effective for thromboprophylaxis in patients at risk of venous thromboembolism.